Prevalence of Peri-Implant Mucositis and Peri-Implantitis in Patients Treated with a Combination of Axial and Tilted Implants Supporting a Complete Fixed Denture - Nicolò Cavalli; Stefano Corbella; Silvio Taschieri; Luca Francetti (The Scientific World Journal)
Objectives. The aim of this retrospective study was to assess the incidence and prevalence of peri-implant mucositis and peri-implantitis in patients with a fixed full-arch prosthesis supported by two axial and two tilted implants. Materials and Methods. Sixty-nine patients were included in the study. Each patient received a fixed full-arch prosthesis supported by two mesial axial and two distal tilted implants to rehabilitate the upper arch, the lower arch, or both. Three hundred thirty-six implants for 84 restorations were delivered. Patients were scheduled for follow-up visits every 6 months in the first 2 years and yearly after. At each follow-up visit peri-implant mucositis and peri-implantitis were diagnosed if present. Results. The overall follow-up range was from 12 to 130 months (mean 63,2 months). Three patients presented peri-implantitis. The prevalence of peri-implant mucositis ranged between 0 and 7,14% of patients (5,06% of implants) while the prevalence of peri-implantitis varied from 0 to 4,55% of patients (3,81% of implants). Conclusions. The prevalence and incidence of peri-implant mucositis and peri-implantitis are lower than most of the studies in literature. Therefore this kind of rehabilitation could be considered a feasible option, on the condition of adopting a systematic hygienic protocol.